Paulo Freire’s dialogic pedagogy and the democratization of pedagogy in Taiwan’s higher education: Challenges and possibilities - Chen, Ming-Kuo; Hsueh, Chia-Ming; Chiang, Wen-Wei; Chiu, Kun-I; Shih, Yi-Huang (Edelweiss Applied Science and Technology, 2025)
This paper advocates for the application of Brazilian educator Paulo Freire’s theory of dialogic education as a critical and transformative framework for reimagining the possibilities of democratic pedagogy within higher education. Freire emphasized that education should be rooted in dialogue, conscientização (critical consciousness), and participatory learning, rejecting the passive conception of learners as mere recipients of knowledge. The integration of Freire’s theory into Taiwan’s higher education context presents an opportunity for academic communities to critically examine prevailing power structures and respond to diverse social voices, thereby fostering democratic pedagogy that is inclusive, civic-minded, and dedicated to the public good. In order to advance the realization of Freire’s vision for democratic pedagogy, structural transformations must be pursued across three pivotal domains: curriculum design, pedagogical practice, and institutional culture. This paper seeks to expand the horizon of democratic pedagogy within Taiwan's higher education through Paulo Freire’s dialogic pedagogy. Interactions between teachers and students should be grounded in love, humility, critical thinking, and faith. Such an approach fosters a hopeful educational environment and contributes to the realization of a more humane and transformative model of higher education pedagogy. Furthermore, within the context of dialogic pedagogy in higher education, the reciprocal exchange and mutual understanding between teachers and students serve as a pathway toward a more holistic and humanized mode of existence.